Meningkatkan Kemampuan Sosial Emosional Melalui Metode Bercerita Dengan Boneka Tangan Pada Anak Usia 5-6 Tahun di PAUD Nurul Hikmah Kabupaten Cianjur - Nina Mulyani; Asep Munajat; Alfian Ashshidiqi Poppyariyana (PT. Alahyan Publisher, 2025)
Improving children's social and emotional development at an early age is very important because it will affect their lives and other aspects of development. Therefore, the best way for teachers to improve children's social and emotional skills is to create a fun learning, teaching, and teaching environment, as well as a good communication environment. This study examines how teachers can use stories to help children learn social and emotional skills. The purpose of this study was to determine how this technique was used to improve the social and emotional skills of children aged 5-6 years at PAUD Nurul Hikmah. In addition, this study also investigated the results of using hand puppets to improve the children's social and emotional skills. This study conducted two cycles, with activities carried out twice each cycle, until the desired completion value of 80% was achieved.